Analysis of Porter’s Generic Strategies in Enhancing Competitiveness in Retail Industry (A Survey on Pajajaran Sindangkasih Minimarket, Ciamis) - Yogi Sugiarto Maulana; Andri Helmi Munawar; Dara Siti Nurjanah (P3M Politeknik Negeri Bali, 2019)
The purpose of this study was to analyze: Porter’s generic strategies in increasing competitiveness in the Pajajaran Sindangkasih Ciamis Minimarket. Suggestions used in this study are qualitative with descriptive methods. The sampling technique used in this study was purposive sampling technique. The research informants were 10 informants who were obtained by owners, unit managers, mentors, cashiers, marketing units, suppliers, customers of the Pajajaran Sindangkasih minimarket, and customers from support. The Porter’s generic strategies applied in the Pajajaran Sindangkasih Minimarket provides discounts for various items in a certain period, lower prices for sponsor products. For the main material products and other general retail products, the average Pajajaran Sindangkasih Minimarket is superior to that. Minimarket Pajajaran Sindangkasih offers services that provide and benefit such as membership cards and groceries, which means there is no other retail promotion. The Focus Strategy of the Pajajaran Sindangkasih Minimarket is used to build competitive advantage in a tighter market segment, by opposing the superiority of the merchandise products offered to customers, which is the basis for better supporting the retail development strategy. Through the evaluation of profits per product, retailers can classify which products are classified as fast selling products (fast moving products) and which products are classified as less salable products (slow moving products).